2014
DOI: 10.1007/s40710-014-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Costs and Benefits of Coastal Water Quality Improvements in the Ko Chang Marine National Park, Thailand

Abstract: The water quality in Ko Chang Marine National Park coast has been problematic for many years. Recently, a conservation plan has been made by the local government for protecting the ocean beaches by constructing a sewage treatment plant in the region. This study uses the contingent valuation method (CVM) to measure the benefits associated with the proposal of the wastewater treatment plant (WWTP), followed by conducting cost-benefit analysis (CBA) in order to justify the feasibility of the public fund appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The improvement of sewage treatment plant technology can not only reduce the environmental pollution, but also reduce the threat to the health of coastal residents and bring a series of social and economic benefits (Birol and Das, 2010). Higher education experience may raise people's concern about environmental protection, which is in accord with previous findings (Piriyapada and Wang, 2014;Cicatiello et al, 2020;Jin and Li, 2020). Additionally, the coefficient of family size is significant at the 1% level, which indicates a negative correlation between family size and WTP.…”
Section: Influence Factors Of the Wtpsupporting
confidence: 76%
“…The improvement of sewage treatment plant technology can not only reduce the environmental pollution, but also reduce the threat to the health of coastal residents and bring a series of social and economic benefits (Birol and Das, 2010). Higher education experience may raise people's concern about environmental protection, which is in accord with previous findings (Piriyapada and Wang, 2014;Cicatiello et al, 2020;Jin and Li, 2020). Additionally, the coefficient of family size is significant at the 1% level, which indicates a negative correlation between family size and WTP.…”
Section: Influence Factors Of the Wtpsupporting
confidence: 76%
“…As remarked by Tziakis et al [10], the construction/upgrade of a wastewater treatment plant must be "approved of" by the residents, who should also be willing to pay for its construction and operation.In this context, in order to evaluate the economic feasibility of the projects, the contingent valuation method (CVM) can be effectively used to enhance the non-market benefits associated with this type of project, for example for recreational and landscape benefits, in order to estimate the total economic value of the investments. It allows the value of non-market goods and services to be determined and is the most widely-used method in evaluating environmental assets by surveying people's willingness to pay for such an asset and/or what they would be willing to receive by way of compensation in order to tolerate such a cost; i.e., preservation of a natural park, or the upgrade of a wastewater treatment plant [11].Numerous studies have been published dealing with the application of CVM in different parts of the world in the case of reclaimed water reuse projects [10,[12][13][14][15][16], sustainable drainage systems and flood risk reduction [17,18], improvement in the surface water quality for nutrient reduction [19], improvement of the water quality used for irrigation needs [20], for coastal water depollution [21], and finally, for tap water quality improvement [22]. Details of these studies are reported in Table 1, together with their aims and main results.…”
mentioning
confidence: 99%
“…Numerous studies have been published dealing with the application of CVM in different parts of the world in the case of reclaimed water reuse projects [10,[12][13][14][15][16], sustainable drainage systems and flood risk reduction [17,18], improvement in the surface water quality for nutrient reduction [19], improvement of the water quality used for irrigation needs [20], for coastal water depollution [21], and finally, for tap water quality improvement [22]. Details of these studies are reported in Table 1, together with their aims and main results.…”
mentioning
confidence: 99%
“…All other countries had 15 or fewer studies, with 57 countries having fewer than five studies (Figure 2; Supplementary Table 4). In terms of scale, the majority of studies (84%) assessed public perceptions at a subnational scale (e.g., Piriyapada and Wang, 2014), with 12% at the national scale (e.g., Goldberg et al, 2016), and only 5% assessed perceptions in more than one country. The largest study assessed ocean perceptions in ten countries (Gelcich et al, 2014).…”
Section: Research Question Data Extracted From Papersmentioning
confidence: 99%